2019
DOI: 10.1038/s41558-019-0622-6
|View full text |Cite
|
Sign up to set email alerts
|

A reversal in global terrestrial stilling and its implications for wind energy production

Abstract: Wind power is a rapidly growing alternative energy source to achieve the goal of the Paris Agreement under the United Nations Framework Convention on Climate Change, to keep warming well below 2 •C by the end of the 21 st century. Widely reported reductions in global average surface wind speed since the 1980s, known as terrestrial stilling, however, have gone unexplained and have been considered a threat to global wind power production. Our new analysis of wind data from in-situ stations worldwide now shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
317
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(366 citation statements)
references
References 44 publications
21
317
2
Order By: Relevance
“…At the global scale, besides northern China, rapid declines in NSWS were also observed in eastern North America, northeastern Europe, Siberia and even over the Tibetan Plateau (You et al 2014, Zeng et al 2018, Zhang et al 2019b, where urbanization is very slow or negligible. A recent study indicated that decadal-scale variations of NSWS was dictated by internal decadal climate variabilities, rather than by the local impact of urbanization (Zeng et al 2019). This is consistent with our key finding that urbanization played a minor role in terrestrial stilling, even in this rapidly developing region.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the global scale, besides northern China, rapid declines in NSWS were also observed in eastern North America, northeastern Europe, Siberia and even over the Tibetan Plateau (You et al 2014, Zeng et al 2018, Zhang et al 2019b, where urbanization is very slow or negligible. A recent study indicated that decadal-scale variations of NSWS was dictated by internal decadal climate variabilities, rather than by the local impact of urbanization (Zeng et al 2019). This is consistent with our key finding that urbanization played a minor role in terrestrial stilling, even in this rapidly developing region.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, Fu et al (2011), Lin et al (2013) and Chen et al (2013) suggested that natural climate variability, such as the Pacific Decadal Oscillation and Arctic Oscillation, may be the primary driver for NSWS change in China. Recently, Zeng et al (2019) found a reversal in global terrestrial wind speed and attributed it to internal decadal atmosphere-ocean oscillations. Compared with the strong decline in NSWS observed at in situ weather stations, NSWS trends derived from reanalysis products and radiosonde records are much weaker (Vautard et al 2010, Chen et al 2013, Lin et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this stilling phenomenon, positive near-surface daily mean wind speed trends have been reported over oceans (Wentz et al 2007), for coastal areas (Pinard 2007), and in high-latitude regions (i.e., .708;McVicar et al 2012;Minola et al 2016). Moreover, after 3-5 decades of stilling, a stabilization or ''recovery'' of global average terrestrial winds commenced in 2013 (Tobin et al 2014) and has continued in the last years (Dunn et al 2016;Azorin-Molina et al 2017Zeng et al 2019). Regional studies have also documented this recent recovery of land surface wind speeds (Kim and Paik 2015;Azorin-Molina et al 2018b;Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another point worth mentioning is that the WRF output used is from a 6-year period in the past. Recent studies show that climate change is causing wind speed patterns to change over relatively short time horizons (on the order of a few decades) that span the planning, construction, and production phases of wind energy plants (Zeng et al, 2019). Could this be an issue, and is it possible to somehow adapt the framework to reliably generate wind demand patterns over the next few decades?…”
Section: The Implications Of Using Numerical Model Output As "Data"mentioning
confidence: 99%